Model Pengajaran Karakter Kejujuran Menggunakan Teknologi Informasi dan Komunikasi (Studi Inovasi Pembelajaran di Pondok Pesantren Al-Azhaar Lubuklinggau) - Mansur, AH; Husaini, Adian; Mujahidin, Endin; Tafsir, Ahmad (Ta'dibuna: Jurnal Pendidikan Islam, 2016)
This study aims to develop a model of honesty teaching using Information and Communication Technology (ICT) in educational institutions of Islamic boarding School. The development of this model is intended to find a teaching model-implementable applicable and adaptable to the circumstances of the boarding school with programs that already exist, structured and based on Islamic values. This study also aims to answer the problems of degradation of morals, ethics and morals recently joined struck boarding school as a result of global transformation so quickly, ahead of human mental readiness in the face. This study uses action research collaborative participatory and quantitative analytical descriptive with one independent variable and one dependent variable. One independent variable is a business act or treatment, which is "Honesty Teaching Model Using Information and Communication Technology", and the dependent variable is the influence of the action; namely the improvement and enhancement of the value of honesty. The subjects of this study are 55 students of Al-Azhaar Islamic Boarding School consist of class one junior and senior high school by involving four teachers as counselors and four collaborators as observers. Measuring devices or media used in this study are instruments in the form of pre-test and post-test as well as programs for the teaching that has taken place in Al-Azhaar Islamic Boarding School with some additions such as honesty canteen and honesty kitchens. As for the character you want to repair in this action research are the values of honesty through six indicators, namely; (1) Discipline (2) Responsibility, (3) Commitments, (4) Consistent (5) Fairness, and (6) Says True. The results of this study stated that "Honesty Teaching Model Using Information and Communication Technologies" very significant influence on attitudes and behavior improvement honest. Where the results of paired t-test between the average value of the pre-test and post-test showed a statistically differ greatly. Thus, the results of this research can be developed and used as a teaching model, especially in Islamic boarding school or in educational institutions boarding. This research gave birth to a concept model of teaching, namely; "Honesty Teaching Model Using Information and Communication Technology" Keywords: Model, Teaching, Honesty, Technology, Information, Communication